2022
DOI: 10.3390/molecules27082430
|View full text |Cite
|
Sign up to set email alerts
|

Removal of Copper(II) in the Presence of Sodium Dodecylobenzene Sulfonate from Acidic Effluents Using Adsorption on Ion Exchangers and Micellar-Enhanced Ultrafiltration Methods

Abstract: The selective removal of Cu(II) in the presence of sodium dodecylobenzene sulfonate from acidic effluents was made using the adsorption and micellar-enhanced ultrafiltration methods. Lewatit MonoPlus TP220 showed the best adsorption behavior in the systems containing Cu(II) in the presence of ABSNa50 surfactant compared to the other adsorbents (removal efficiency ≈ 100%, sorption capacity ≈ 10 mg/g). The kinetics followed the pseudo-second order kinetic equation. The Langmuir adsorption capacities were 110 mg/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 75 publications
0
2
0
Order By: Relevance
“…Due to the toxic nature of copper, this effluent must be treated before being discharged into the environment. As with other heavy metals, several physicochemical methods are proposed for this purpose, including adsorption, ion exchange, extraction, and membrane techniques [ 59 ]. Most of the recent literature on Cu removal by membrane filtration techniques is based on model solutions.…”
Section: Removal Of Heavy Metalsmentioning
confidence: 99%
“…Due to the toxic nature of copper, this effluent must be treated before being discharged into the environment. As with other heavy metals, several physicochemical methods are proposed for this purpose, including adsorption, ion exchange, extraction, and membrane techniques [ 59 ]. Most of the recent literature on Cu removal by membrane filtration techniques is based on model solutions.…”
Section: Removal Of Heavy Metalsmentioning
confidence: 99%
“…EDX spectra showed that FeS consisted mostly of C and Fe (Figure 1). This result can be referred to the fact that the adsorption mechanism of Cu 2+ ions may be due to ion exchange [7,15].…”
Section: Fes Morphological Element Analysismentioning
confidence: 99%
“…EDX spectra showed that FeS consisted mostly of C and Fe (Figure 1). This result can be referred to the fact that the adsorption mechanism of Cu 2+ ions may be due to ion exchange [7,15]. In the FTIR analysis of adsorbent molecules, the two regions are defined as the functional group region (4000-1500 cm −1 ) and the fingerprint region (1500-500 cm −1 ).…”
Section: Fes Morphological Element Analysismentioning
confidence: 99%
“…These studies are essential not only for the cognitive effect but also for the application. There are a number of applications for such systems that contain surfactants and metal ions, for example, cloud point extraction [13][14][15], micellar enhanced ultrafiltration [16][17][18], ion exchange [19,20], bitumen emulsion technology [21], leaching [22], continuous countercurrent foam separation [3,11] and flotation in mineral processing [23][24][25], as well as adsorption using surfactant-modified beads [26] and polymersurfactant aggregates [27] or selective precipitation in the presence of surfactants [28]. It should be also noted that the extensive use of both surfactants and metals also contributes to their presence in wastewater.…”
Section: Introductionmentioning
confidence: 99%